Mitigation of antibiotic resistance risk in aerobic sludge by zero-valent iron: From pathogen reduction to conjugation inhibition and network weakening - Ying Wu; Lin Zhu; Guoping Lin; Xuezhu Han; Jingpeng Li; Jiaming Yi; Dan Huang; Meizhen Wang (Bioresource Technology, 2026)

Osteoprotective effect of Perinereis aibuhitensis ultrasound-assisted aqueous extract against retinoic acid-induced osteoporosis in mice - Biliang Mo; Xinxia Song; Jianmeng Liao; Xiaoyu Xia; Hongyu Lu; Wenhong Cao; Zhongqin Chen; Mingtang Tan; Huina Zheng; Jialong Gao; Haisheng Lin; Zhihong Zheng; et al. (Food Bioscience, 2026)

Bacteria–polysaccharide interfacial regulation by calcium alginate hydrogel capsules supports sulfate reduction in acidic water - Yujie Wang; Fangzhou Luo; Zhaoyue Yang; Zhenghua Liu; Huachan Lin; Xiyu Liu; Min Zhang; Guoping Jiang; Lei Zhou; Lechang Xu; Delong Meng; Qingyun Yan; et al. (Carbohydrate Polymers, 2026)

The sustained expansion (2011−2022) and abrupt contraction (2023) of the Ross Sea polynyas - Xiaolu Ou; Lingqiao Cheng; Dongming Lin; Guoping Zhu (Journal of Marine Systems, 2026)

Magnetic field-assisted freezing mitigates quality deterioration in oyster meat (Crassostrea hongkongensis) by inducing the formation of uniform ice crystals and preserving water-holding capacity - Weisheng Jian; Jialong Gao; Xiaoyu Xia; Wenhong Cao; Haisheng Lin; Huina Zheng; Guoping Zhu; Zhihong Zheng (Food Chemistry, 2026)

Effects of heat treatment on the characteristics of low-molecular-weight oyster peptides (LOPs) W1/O/W2 double emulsions: Physicochemical, interfacial, and rheological properties - Xiaolin Guo; Wanqi Chen; Wenhong Cao; Haisheng Lin; Zhongqin Chen; Jialong Gao; Guoping Zhu; Mingtang Tan; Ming Cheng; Huina Zheng (Food Chemistry, 2026)

Heavy-metal and nutrient enrichment triggered a regime shift in marsh diatom assemblages over the past millennium - Dongxue Han; Jinxin Cong; Lin Li; Guoping Wang; Chuanyu Gao (Journal of Environmental Management, 2026)

Food-grade abalone muscle hydrolysates as affected by high-pressure homogenization: An in-depth investigation into air-water interfacial behavior of their proteins - Jinzhen Li; Wanyi Wu; Wenhong Cao; Haisheng Lin; Jialong Gao; Mingtang Tan; Zhongqin Chen; Guoping Zhu; Huina Zheng (Food Chemistry, 2026)

Assessment of the severity of lower extremity peripheral arterial disease based on gastrocnemius surface electromyography and mechanomyography signals - Wenxuan Sun; Yanbin Guo; Shuwei Lin; Guoping Wang; Youpeng Zhu; Yao Zhang; Ye Du; Zibo Feng (Medical & Biological Engineering & Computing, 2026)

Microbial biofilm-based hydrovoltaic system for degradating organic pollutants - Zihan Lin; Guoping Ren; Yuanhong Guo; Xiang Shen; Qichang Hu; Shungui Zhou (Water Research, 2026)

Temperature-dependent gelation of oyster protein: Structural insights and network formation mechanisms - Yu Liu; Mingtang Tan; Zhongqin Chen; Huina Zheng; Jialong Gao; Haisheng Lin; Guoping Zhu; Wenhong Cao (Food Hydrocolloids, 2026)

Insight into the synergistic inhibition of oyster pentapeptide (Phe-Pro-Val-Gly-Arg) and peonidin-3-O-glucoside against DPP-IV and their interactions - Xiaojie Su; Mengmeng Zhang; Wenhong Cao; Longjian Zhou; Mingtang Tan; Guoping Zhu; Jialong Gao; Haisheng Lin; Zhongqin Chen (Food Research International, 2026)

Environmental stressors in seafood supply chains: From molecular mechanisms to advanced preservation strategies - Weisheng Jian; Jialong Gao; Xiaoyu Xia; Wenhong Cao; Xiaoming Qin; Haisheng Lin; Zhongqin Chen; Huina Zheng; Guoping Zhu; Zhihong Zheng (Food Chemistry, 2025)

Oyster (Crassostrea hongkongensis) protein isolates: Influence of extraction pH on physicochemical, conformational and functional properties - Yu Liu; Mingtang Tan; Zhongqin Chen; Huina Zheng; Jialong Gao; Haisheng Lin; Guoping Zhu; Wenhong Cao (Food Chemistry, 2025)

A knowledge-guided LSTM reservoir outflow model and its application to streamflow simulation in reservoir-regulated basins - Runting Chen; Dagang Wang; Yiwen Mei; Yongen Lin; Zequn Lin; Zhi Zhang; Shengjie Zhuang; Jinxin Zhu; Jonghun Kam; Yiping Wu; Guoping Tang (Journal of Hydrology, 2025)

Unveiling the components, physiological functions and emerging trends of hydroxycinnamic acid amides in goji berry (Lycium) - Siyuan Wei; Yuying Wang; Shiyu Zhou; Shina Luo; Yunuo Lin; Ruixi Wang; Qinyue Jia; Tingting Feng; Guoping Zhao; Xuefeng Yin; Fangwei Yang (Food Research International, 2025)

In silico prospecting of ADH activating peptides from Pacific oyster (Crassostrea gigas) and protective effect on ethanol-induced damage in HepG2 cells - Yajing Chen; Xiuli Zhang; Zhihong Zheng; Wenhong Cao; Xiaoming Qin; Haisheng Lin; Zhongqin Chen; Huina Zheng; Guoping Zhu; Jialong Gao (Food Chemistry, 2025)

Effect of steaming on the selenium form, structure, and bioavailability of selenopolysaccharides from Chlamys nobilis - Junyang Yang; Junting Cai; Zhongqin Chen; Mingtang Tan; Huina Zheng; Jialong Gao; Haisheng Lin; Guoping Zhu; Wenhong Cao (Food Chemistry, 2025)

Customized screening of ACE2 regulatory peptides from oyster to mitigate LPS-induced acute lung injury based on SPR technology - Xiaoyu Xia; Caixing Wen; Wenhong Cao; Xiaoming Qin; Yujin Li; Haisheng Lin; Zhongqin Chen; Huina Zheng; Guoping Zhu; Jialong Gao (Food Bioscience, 2025)

Spatiotemporal evolution characteristics of ecological niche fitness in regional innovation ecosystem: province-level evidence from China - Neng Shen; Guoping Zhang; Lin Zhang; Johnny F. I. Lam; Linjie Feng (Environmental Monitoring and Assessment, 2025)

Can digitalization break the political resource curse? A study on political connections and corporate green innovation - Neng Shen; Lin Zhang; Hao Huang; Guoping Zhang; Jing Zhang; Jingwen Zhou (Journal of Environmental Management, 2025)

Mendelian randomization analysis and molecular mechanism study of childhood asthma and obstructive sleep apnea - Xinyu Wang; Lin Zhang; Hao Chen; Ting Tian; Lulu Wu; Yuping Huang; Qian Cao; Lili Zhuang; Guoping Zhou (Human Genetics, 2025)

Microscale fluvial landscape evolution and its impacts on early human settlement at the Shangshan cultural site in the upper Qiantang region, eastern China - Wenjia Zhang; Zhou Lin; Guoping Zhang; Leping Jiang; Meiling Chen; Shengchao Zhou; Yuchen Zhang; Xiang Zhao (Geomorphology, 2025)

Recent advances in taste transduction mechanism, analysis methods and strategies employed to improve the taste of taste peptides - Chunyong Song; Zhijun Wang; Hanqi Li; Wenhong Cao; Zhongqin Chen; Huina Zheng; Jialong Gao; Haisheng Lin; Guoping Zhu (Critical Reviews in Food Science and Nutrition, 2025)

How does data factor marketization influence urban carbon emission efficiency? A new method based on double machine learning - Neng Shen; Jingwen Zhou; Guoping Zhang; Lianjun Wu; Lin Zhang (Sustainable Cities and Society, 2025)

Impact of DNA Extraction Methods on Gut Microbiome Profiles: A Comparative Metagenomic Study - Yanni Pu; Xiaofeng Zhou; Hao Cai; Tao Lou; Chenglin Liu; Mengmeng Kong; Zhonghan Sun; Yanren Wang; Ruyi Zhang; Yuxuan Zhu; Lin Ye; Yuanting Zheng; et al. (Phenomics, 2025)

Can big data policy drive urban carbon unlocking efficiency? A new approach based on double machine learning - Neng Shen; Guoping Zhang; Jingwen Zhou; Lin Zhang; Lianjun Wu; Jing Zhang; Xiaofei Shang (Journal of Environmental Management, 2024)

Distribution and response of electroactive microorganisms to freshwater river pollution - Shan Yang; Meijun Dong; Lizhou Lin; Bo Wu; Youda Huang; Jun Guo; Guoping Sun; Shaofeng Zhou; Meiying Xu (Environmental Pollution, 2024)

Preparation of cementing material and recovery of iron resources using converter slag - Shuai Hao; Guoping Luo; Lin Wang; Shengli An; Yifan Chai; Wei Song (Process Safety and Environmental Protection, 2024)

Effect of baking on the structure and bioavailability of protein-binding zinc from oyster (Crassoetrea hongkongensis) - Chunyong Song; Runfang Zhong; Shan Zeng; Zhongqin Chen; Mingtang Tan; Huina Zheng; Jialong Gao; Haisheng Lin; Guoping Zhu; Wenhong Cao (Food Chemistry, 2024)

Improving Granulosa Cell Function in Premature Ovarian Failure with Umbilical Cord Mesenchymal Stromal Cell Exosome-Derived hsa_circ_0002021 - Ge Yang; Bo Zhang; Mei Xu; MingJun Wu; Jie Lin; ZiYu Luo; YueHua Chen; Qin Hu; GuoPing Huang; HaiYan Hu (Tissue Engineering and Regenerative Medicine, 2024)

Establishing Virtual Bioequivalence and Clinically Relevant Specifications for Omeprazole Enteric-Coated Capsules by Incorporating Dissolution Data in PBPK Modeling - Ruwei Yang; Yaqi Lin; Kaifeng Chen; Jie Huang; Shuang Yang; An Yao; Xiaoyan Yang; Deqing Lei; Jing Xiao; Guoping Yang; Qi Pei (The AAPS Journal, 2024)

Carboxymethyl cellulose and carboxymethyl chitosan-based composite nanogel as a stable delivery vehicle for oyster peptides: Characterization, absorption and transport mechanism - Pei Zhang; Zhongqin Chen; Longjian Zhou; Jialong Gao; Huina Zheng; Haisheng Lin; Guoping Zhu; Xiaoming Qin; Wenhong Cao (Food Chemistry, 2024)

Chinese Society of Cardiology guidelines on the diagnosis and treatment of adult fulminant myocarditis - Jiangang Jiang; Hongyang Shu; Dao Wen Wang; Rutai Hui; Chenze Li; Xiao Ran; Hong Wang; Jing Zhang; Shaoping Nie; Guanglin Cui; Dingcheng Xiang; Qun Shao; et al. (Science China Life Sciences, 2024)

Dynamic changes of zinc chemical speciation and zinc-containing peptides release in oysters (Crassostrea hongkongensis) during enzymatic hydrolysis - Ran Du; Wan Li; Jiawei Li; Shan Zeng; Zhongqin Chen; Jialong Gao; Huina Zheng; Haisheng Lin; Guoping Zhu; Xiaoming Qin; Wenhong Cao (Food Bioscience, 2024)

Establishing a pulmonary aspergillus fumigatus infection diagnostic platform based on RPA-CRISPR-Cas12a - Chunhui Lin; Jing Zhou; Nana Gao; Runde Liu; Ge Li; Jinyu Wang; Guoping Lu; Jilu Shen (World Journal of Microbiology and Biotechnology, 2024)

Ecosystem services in the typical black soil region of Northeastern China: implications for the optimal land use pattern - Lin Feng; Ziyang Yu; Guoping Lei (Environment, Development and Sustainability, 2024)

Exploring ecological carbon sequestration advantage and economic responses in an ecological security pattern: A nature-based solutions perspective - Lin Wang; Junsan Zhao; Yilin Lin; Guoping Chen (Ecological Modelling, 2024)

Investigation of the soil arching evolution in the ground with or without a tunnel - Rui-Xiao Zhang; Dong Su; Xing-Tao Lin; Tai-Feng Zhu; Guoping Lei; Xiang-Sheng Chen (Transportation Geotechnics, 2023)

The full-length genome sequence of a novel amalgavirus in Lilium spp. in China - Yanyan Huo; Xiaoting Li; Jiale Zhou; Shengjie Lin; Jiahao Ding; Huan Liu; Jianglian Yu; Ni Hong; Guoping Wang; Fang Ding (Archives of Virology, 2022)

Developmental Origins of Human Cortical Oligodendrocytes and Astrocytes - Lin Yang; Zhenmeiyu Li; Guoping Liu; Xiaosu Li; Zhengang Yang (Neuroscience Bulletin, 2022)
Human cortical radial glial cells are primary neural stem cells that give rise to cortical glutaminergic projection pyramidal neurons, glial cells (oligodendrocytes and astrocytes) and olfactory bulb GABAergic interneurons. One of prominent features of the human cortex is enriched with glial cells, but there are major gaps in understanding how these glial cells are generated. Herein, by integrating analysis of published human cortical single-cell RNA-Seq datasets with our immunohistochemistical analyses, we show that around gestational week 18, EGFR-expressing human cortical truncated radial glial cells (tRGs) give rise to basal multipotent intermediate progenitors (bMIPCs) that express EGFR, ASCL1, OLIG2 and OLIG1. These bMIPCs undergo several rounds of mitosis and generate cortical oligodendrocytes, astrocytes and olfactory bulb interneurons. We also characterized molecular features of the cortical tRG. Integration of our findings suggests a general picture of the lineage progression of cortical radial glial cells, a fundamental process of the developing human cerebral cortex.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Wave-ice dynamical interaction: a numerical model and its application - Yang Zhang; Changsheng Chen; Guoping Gao; Jianhua Qi; Huichan Lin; Wei Yu; Liang Chang (Acta Oceanologica Sinica, 2021)

Transcription Factor VAX1 Regulates the Regional Specification of the Subpallium Through Repressing Gsx2 - Yan Wen; Zihao Su; Ziwu Wang; Lin Yang; Guoping Liu; Zicong Shang; Yangyang Duan; Heng Du; Zhenmeiyu Li; Yan You; Xiaosu Li; Zhengang Yang; et al. (Molecular Neurobiology, 2021)

Decoding Cortical Glial Cell Development - Xiaosu Li; Guoping Liu; Lin Yang; Zhenmeiyu Li; Zhuangzhi Zhang; Zhejun Xu; Yuqun Cai; Heng Du; Zihao Su; Ziwu Wang; Yangyang Duan; Haotian Chen; et al. (Neuroscience Bulletin, 2021)
Mouse cortical radial glial cells (RGCs) are primary neural stem cells that give rise to cortical oligodendrocytes, astrocytes, and olfactory bulb (OB) GABAergic interneurons in late embryogenesis. There are fundamental gaps in understanding how these diverse cell subtypes are generated. Here, by combining single-cell RNA-Seq with intersectional lineage analyses, we show that beginning at around E16.5, neocortical RGCs start to generate ASCL1 + EGFR + apical multipotent intermediate progenitors (MIPCs), which then differentiate into basal MIPCs that express ASCL1, EGFR, OLIG2, and MKI67. These basal MIPCs undergo several rounds of divisions to generate most of the cortical oligodendrocytes and astrocytes and a subpopulation of OB interneurons. Finally, single-cell ATAC-Seq supported our model for the genetic logic underlying the specification and differentiation of cortical glial cells and OB interneurons. Taken together, this work reveals the process of cortical radial glial cell lineage progression and the developmental origins of cortical astrocytes and oligodendrocytes.

Sideswiping Tropical Cyclones and Their Associated Precipitation over China - Tian Feng; Fumin Ren; Da-Lin Zhang; Guoping Li; Wenyu Qiu; Hui Yang (Advances in Atmospheric Sciences, 2020)

Optimized trio genome sequencing (OTGS) as a first-tier genetic test in critically ill infants: practice in China - Huijun Wang; Yulan Lu; Xinran Dong; Guoping Lu; Guoqiang Cheng; Yanyan Qian; Qi Ni; Ping Zhang; Lin Yang; Bingbing Wu; Wenhao Zhou (Human Genetics, 2020)

Life cycle assessment of preserved plum production in Southern China - Xiaobo Xue Romeiko; Shao Lin; Guoping Huang (Clean Technologies and Environmental Policy, 2020)

Anthropogenic impacts in the Changbai Mountain region of NE China over the last 150 years: geochemical records of peat and altitude effects - Kunshan Bao; Guoping Wang; Lin Jia; Wei Xing (Environmental Science and Pollution Research, 2019)

Ovarian development in Argentinean shortfin squid Illex argentinus: group-synchrony for corroboration of intermittent spawning strategy - Dongming Lin; Xinjun Chen; Yong Chen; Guoping Zhu; Jizhou Yan (Hydrobiologia, 2017)

Whole transcriptome analysis of three leaf stages in two cultivars and one of their F1 hybrid of Camellia sinensis L. with differing EGCG content - Jinke Lin; Iain W. Wilson; Guoping Ge; Guiling Sun; Fuliang Xie; Yanfang Yang; Liangyu Wu; Baohong Zhang; Jianqiang Wu; Yue Zhang; Deyou Qiu (Tree Genetics & Genomes, 2017)

Quantifying the changing properties of climate extremes in Guangdong Province using individual and integrated climate indices - Yanhu He; Kairong Lin; Guoping Tang; Xiaohong Chen; Shenglian Guo; Faliang Gui (International Journal of Climatology, 2017)
The temporal and spatial trends of four climate extreme indices for Guangdong Province of China were calculated based on observed daily precipitation, daily maximum, and daily minimum temperatures at 24 weather stations as well as the frequency of typhoon events during the period of 1957–2013. An integrated extreme climatic index ( IECI ) was derived from four individual climate extreme indices (high temperature days ( H td ), low temperature days ( L td ), intensive precipitation days ( I pd ) and number of typhoon events ( TT )), considering their weights using an information theory model. A simple linear regression model was utilized to analyze the spatiotemporal trends of the climate extremes. The correlation analysis between the above extreme climatic indices and the socioeconomic losses [affected area of crops ( AAC ), direct losses of the economy ( DLE ), and affected population ( AP )] was calculated. The results indicate that H td increased while L td decreased significantly at the 5% significance level. By contrast, there were no significant long‐term changes in I pd and TT . The rate of change of IECI was 0.006 per decade and no long‐term trend was detected in IECI . Spatially, a positive trend was observed in the Yuexi River Basin ( YXRB ) for I pd , while a negative trend was found in the East River Basin ( ERB ). L td followed an opposite spatial pattern to that of H td . Extreme temperature days occurred more frequently in the Pearl River Delta ( PRD ) than in other parts of Guangdong Province. Regions with positive IECI rates of change were mostly in the YXRB , the coastal area of the Yuedong River Basin ( YDRB ) and the northern and southern part of the ERB . The correlation coefficients between IECI and AAC , DLE , and AP are 0.375, 0.424 and 0.603, respectively. In general, IECI correlated more strongly with the loss indices caused by extreme climatic events than did the four individual extreme climatic indices.

QTL analysis of three flower-related traits based on an interspecific genetic map of Luffa - Junjie Cui; Jiaowen Cheng; Guoping Wang; Xin Tang; Zhiming Wu; Mingbao Lin; Lianfang Li; Kailin Hu (Euphytica, 2015)

Effects of crude oil contamination on soil physical and chemical properties in Momoge wetland of China - Ying Wang; Jiang Feng; Qianxin Lin; Xianguo Lyu; Xiaoyu Wang; Guoping Wang (Chinese Geographical Science, 2013)

The C161T polymorphism in the peroxisome proliferator-activated receptor gamma gene (PPARγ) is associated with risk of coronary artery disease: a meta-analysis - Zhijun Wu; Yuqing Lou; Wei Jin; Yan Liu; Lin Lu; Guoping Lu (Molecular Biology Reports, 2013)

FVCOM model estimate of the location of Air France 447 - Changsheng Chen; Richard Limeburner; Guoping Gao; Qichun Xu; Jianhua Qi; Pengfei Xue; Zhigang Lai; Huichan Lin; Robert Beardsley; Breck Owens; Barry Carlson (Ocean Dynamics, 2012)

Grain-size characteristics of sediment in Daniugou peatland in Changbai Mountains, Northeast China: Implications for atmospheric dust deposition - Kunshan Bao; Lin Jia; Xianguo Lu; Guoping Wang (Chinese Geographical Science, 2010)

Sodium butyrate-induced upregulation of p18 INK4C gene affects K562 cell G0/G1 arrest and differentiation - Lin Li; Guoping Zhang; Ye Zhang; Jiang Tan; Hui Huang; Baiqu Huang; Jun Lu (Molecular and Cellular Biochemistry, 2008)